2018
DOI: 10.1021/acsmedchemlett.8b00315
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Retigabine Derivatives as Potent KCNQ4 and KCNQ5 Channel Agonists with Improved Specificity

Abstract: Recent research suggests that KCNQ isoforms, particularly the KCNQ4 and KCNQ5 subtypes expressed in smooth muscle cells, are involved in both establishing and maintaining resting membrane potentials and regulating smooth muscle contractility. Retigabine (RTG) is a first-in-class antiepileptic drug that potentiates neuronal KCNQ potassium channels, but poor subtype selectivity limits its further application as a pharmacological tool. In this study, we improved the subtype specificity of retigabine by altering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…As other KCNQ channels are involved in the physiology of diverse tissues and may also be associated with diseases, lack of specificity would lead to unwanted side-effects. As such, the selectivity for KCNQ4 could be achieved by the further refinement of existing compounds, as shown previously [ 76 ]. Based on the delineation of the crucial residues of the specific binding of retigabine with KCNQ4 and the molecular details of its activation [ 71 ], the discovery and optimization of related chemicals would be accelerated.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…As other KCNQ channels are involved in the physiology of diverse tissues and may also be associated with diseases, lack of specificity would lead to unwanted side-effects. As such, the selectivity for KCNQ4 could be achieved by the further refinement of existing compounds, as shown previously [ 76 ]. Based on the delineation of the crucial residues of the specific binding of retigabine with KCNQ4 and the molecular details of its activation [ 71 ], the discovery and optimization of related chemicals would be accelerated.…”
Section: Discussionmentioning
confidence: 87%
“…Wang et al reported several compounds that were made by modifying retigabine and showed better selectivity for KCNQ4 and KCNQ5 [ 76 ]. For instance, a N-1/3 substitution resulted in improved specificity for KCNQ4 and KCNQ5 compared with naïve retigabine [ 76 ].…”
Section: Kcnq4 Activatorsmentioning
confidence: 99%
See 3 more Smart Citations